Proceedings of the 2014 International Conference on Control, Instrumentation, Energy and Communication (CIEC) 2014
DOI: 10.1109/ciec.2014.6959106
|View full text |Cite
|
Sign up to set email alerts
|

Optimal location and sizing of DG to minimize loss of distribution system using SIMBO-Q method

Abstract: Determination of optimal location and size of Distributed Generation units is one of the major problems of distribution network. Optimum locations and sizes of DG sources have profoundly impacted on the system losses of a distribution network. This paper presents a new optimization technique known as Swine Influenza Model Based Optimization with Quarantine (SIMBO-Q) to determine optimal allocation and sizing of distributed generation units in distribution network to minimize active power loss. SIMBO-Q performs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Modified Teaching-Learning Based Optimization algorithm is proposed to determine optimal sizing and location of DG units [8]. Swine Influenza model based optimization with Quarantine method is used to determine optimal location and sizing of DG to minimize losses of the distribution system [9]. The optimal location and size of DG units are obtained based on voltage stability index (VSI) by Particle Swarm Optimization in [10].…”
Section: Introductionmentioning
confidence: 99%
“…Modified Teaching-Learning Based Optimization algorithm is proposed to determine optimal sizing and location of DG units [8]. Swine Influenza model based optimization with Quarantine method is used to determine optimal location and sizing of DG to minimize losses of the distribution system [9]. The optimal location and size of DG units are obtained based on voltage stability index (VSI) by Particle Swarm Optimization in [10].…”
Section: Introductionmentioning
confidence: 99%
“…Onlooker bees evaluate the nectar information brought by employed bees and choose a nectar position with a certain probability related to its nectar amount. The probability of a nectar chosen by onlooker bees is determined by the following expression: (7) where fit i is the fitness value of i-th solution; N is the number of nectar sources. It can be concluded that the higher fitness value of the nectar source, the greater probability of selection by onlooker bees .…”
Section: Artificial Bee Colony Algorithmmentioning
confidence: 99%
“…A method called Harmony Search Algorithm is applied to minimize losses in [5]. Other methods used in DG planning are Hereford Ranch Algorithm (HRA) [6], Swine Influenza Model Based Optimization with Quarantine (SIMBO-Q) [7], Fuzzy Evolutionary Programming algorithm (Fuzzy-EP) [8], etc.…”
Section: Introductionmentioning
confidence: 99%